To determine which student is incorrect, let's carefully analyze both their approaches to solving the quadratic equation \( x^2 + 4x - 5 = 7 \).
-
Rearranging the Equation: Both students correctly start by rearranging the initial equation \( x^2 + 4x - 5 = 7 \) to set it equal to zero: \[ x^2 + 4x - 5 - 7 = 0 \implies x^2 + 4x - 12 = 0 \quad \text{(correctly done by Jamal)} \]
-
Factoring:
- Jamal's factors: He factored the equation as \( (x+6)(x-2) = 0 \).
- George's factors: He incorrectly wrote the factors as \( (x+5)(x-1) = 0 \).
Let's verify the correct factors of \( x^2 + 4x - 12 \): To factor \( x^2 + 4x - 12 \), we look for two numbers that multiply to \(-12\) (the constant term) and add up to \(4\) (the coefficient of \(x\)). The numbers \(6\) and \(-2\) satisfy this requirement: \[ (x + 6)(x - 2) = 0 \] So, Jamal's factoring is correct, and he finds the solutions \( x = -6 \) and \( x = 2 \).
Now, we can also verify the factors that George provided for the original equation \( x^2 + 4x - 12 \): George's factors, \( (x + 5)(x - 1) \), result in: \[ x^2 - 1 + 5x - 5 = x^2 + 4x - 5 \] That's incorrect for the equation at hand. Therefore, George's factorization is not valid.
- Solutions:
- Jamal finds the solutions as \( x = -6 \) and \( x = 2 \).
- George finds the incorrect solutions as \( x = -5 \) and \( x = 1 \).
Conclusion: George is the incorrect student. His initial factorization of the quadratic \( x^2 + 4x - 12 = 0 \) was erroneous, leading him to the wrong solutions. The correct roots are obtained from Jamal’s accurate factorization \( (x + 6)(x - 2) = 0 \), leading to \( x = -6 \) and \( x = 2 \).